Reducing Wastages in Pump Manufacturing Processes through Lean Manufacturing Concept - Jeevabharathi, S. (International Journal of Psychosocial Rehabilitation, 2019)
Lean manufacturing is a systematic approach to process improvement. The method is based on finding and reducing waste coupled with continuous improvement. It was first developed by Toyota but is now applied to many diverse industries and businesses. An attempt has been made to apply lean manufacturing methodology in a leading pump manufacturing company, analyzing the seven wastes, namely overproduction, defects and their correction, inventory, transportation, waiting, motion, and overprocessing. The work concentrates on the activities in the fettling, winding section, component stores, and assembly section. To determine and reduce defects in the winding section, a cause-and effects diagram is constructed. Comparisons are made on quality and productivity before and after implementing lean manufacturing. Proper transportation, material handling, and storage systems are proposed to improve quality in fettling operations. Kanban cards are introduced to control the inventory level in stores, reducing waste.